Study on Some Groups Whose Elements Are Symmetries of Geometric Objects - Ola Mohammed; Abdalftah Elbori; Muna Abdulhafed (AlQalam Journal of Medical and Applied Sciences, 2024)
In this paper discuses some important examples of non-abelian groups whose elements are symmetries of geometric objects, which is called dihedral group D_2n, and uses them on some chemical compounds to understand how their atoms vibrate. As we know chemists and mineralogists study dihedral groups in order to classify the structure of molecules and crystals, respectively. Farther more, to study the vibration of atoms of some chemical compounds, we will represent them as geometrical shapes that correspond to the number and arrangement of their atoms in the molecule, with the same angle of binding. يتناول هذا البحث بعض الأمثلة المهمة للمجموعات غير الابدالية التي تكون عناصرها متناظرة من الأجسام الهندسية، والتي تسمى المجموعة ثنائية السطوح، ويستخدمها على بعض المركبات الكيميائية لفهم كيفية اهتزاز ذراتها. كما نعلم، يقوم الكيميائيون وعلماء المعادن بدراسة المجموعات ثنائية السطوح من أجل تصنيف بنية الجزيئات والبلورات، على التوالي. علاوة على ذلك، لدراسة اهتزاز ذرات بعض المركبات الكيميائية، سنمثلها بأشكال هندسية تتوافق مع عدد ذراتها وترتيبها في الجزيء، وبنفس زاوية الارتباط.